Analisis perbandingan rencana strategi Baitul Maal wat Tamwil di Jawa dan Sumatera - Yahya, Syafi' Ainul; Taufiqi, Ahmad Roni (Maliki Interdisciplinary Journal, 2023)
This research aims to analyze a comparison of strategic plans between BMT Taruna Sejahtera Mijen Semarang, BMT Al Falah Cirebon, and BMT Al Fattah Kota Solok based on the number of programs and activities. This study employs a qualitative descriptive approach, with data obtained from journals and the internet. Subsequently, data analysis is conducted using tabular presentation and analysis. The research findings conclude that, in terms of strategic planning, these three BMTs exhibit differences in terms of development programs, marketing, and other activities. However, they share a common goal, which is to advance as BMTs in order to fulfill the economic empowerment and welfare of the communities surrounding them.